Evaluation of genetic variations and phylogeny of the most popular pear (Pyrus communis L.) cultivars in Duhok city using AFLP markers - Ali, Shaymaa H.; Othman, Hemin E.; Abdullah Zibari, Payman A.; S. Jubrael, Jaladet M. (Innovaciencia, 2018)
Introduction: Genotyping and evaluation of genetic variation and polymorphic information content of the locally cultivated pear (Pyrus communis L.) might play an important role in building the genetic bank. These are also immensely important for present and future pear breeding program in the region. Methods: In the current study, AFLP markers have been employed to estimate the level of genetic diversity and to assess the phylogeny among theseven most popular pear cultivars in Duhok city. Results: Eight selective primer combinations generated a total of 653 AFLP fragments from which 445 (68.2%) fragments were polymorphic. The number of visible amplified products per primer combination were varied and ranged from 66 to 96 bands. The highestpercentage of polymorphism (78.4%) was observed by the primer pair P174/M182, while the lowest percentage of polymorphism (58.6%) was observed by the primer pair P174/M100. The highest PIC (0.85) was obtained with the primer combination P174/ M182, while, the lowest PIC (0.49) was obtained by the primer combination P174/M307. The genetic distance was ranged from 0.1348 (between Danimarki and Amreki cultivars) to 0.3131 (between Italy and Zaafaran2 cultivars). Based on the AFLP data, all the seven pear genotypes were successfully clustered into two separate clusters (C1 and C2) with an out-group of Itali cultivar. Conclusions: Overall, it can be concluded that there was high polymorphism among the studied genotypes. Also, it can be stated that the AFLP was a reliable and a powerful technique in genotyping and discriminating of respective pear cultivars.
Keywords: Pear (Pyrus communis L.); AFLP; Genetic diversity; Phylogeny.